How Does Leader Empowering Behavior Promote Employee Knowledge Sharing? The Perspective of Self-Determination Theory - Xiang, Shuting; Zhang, Yuan; Ning, Nan; Wu, Shan; Chen, Weiru (Frontiers in Psychology, 2021)
Although scholars have recognized the important role of leader empowering behavior in promoting employee knowledge sharing, investigations on the potential underlying mechanism are still limited. To enrich studies revealing the possible underlying paths, drawing on self-determination theory, this paper proposes a moderated mediation model. We propose that employee self-determination plays a mediating role and employee proactivity moderates the mediating effect. We test our hypotheses based on data collected from 230 employees across a three-wave study. The empirical results demonstrate that leader empowering behavior promotes employee knowledge sharing by enhancing employee self-determination. Employees’ proactive personality moderates the indirect effect such that the indirect effect is stronger when employees have high levels of proactive personality. This paper thus contributes to the related literature and reveals practical implications.